Effect of bone and joint resposition massage on reducing neck pain syndrome in farm workers - Hidayatulah, Muhammad Riyan; Anam, Khaerul (Jurnal Porkes, 2024)
Neck pain is a condition of injury to the soft tissue of the muscles, nerves, blood vessels, lymphatic Neck pain can be caused by several factors, including a sitting position that is too long, the wrong sleeping position, a hard impact on the neck, and pressure on muscles, nerves, bones and joints due to excessive lifting so that muscle stiffness occurs. The aim to be achieved in this study is to determine the effect of repositioning bones and joints (RTS) massage on reducing neck pain (Neck Pain Syndrome) in agricultural workers in Mesanggok Village Kec. Gerung Kab. West Lombok ". This study used a pre-experimental method with a one group pretest posttest design. The population in this study were 15 agricultural workers. The sampling technique used was purposive sampling. Data collection by measuring the Pain variable using the Visual Analogue Scale (VAS) measuring instrument. Data analysis using the T-test formula. The results showed that the results of the posttest based on the formula "t-test" obtained t count is 4.599 which is compared with t table at a significance level of 5% at degrees of freedom n-1 (15-1 = 14) which is 1.761. Because t coun t > t table (4.599 >1.761) then the working hypothesis is accepted so it can be concluded that "there is an effect of massage method repositioning bones and joints (RTS) on Decreasing Neck Pain Syndrome in Farm Labourers in Mesanggok Village, Gerung District, West Lombok Regency".